Africa's liberation generation. Issue 3 (September 2022) - Rotberg, Robert I.
Abstract : Today's African political class is much more diverse in character and aspiration than the one that overcame colonial rule and inaugurated independent governments. Sons of early liberation leaders now jostle for power in a few countries (Chad, Kenya), descendants of successful autocrats perpetuate family rule in others (Gabon), several long-serving hegemons remain in control after decades in office (as in Cameroon, Djibouti, Rwanda and Uganda), a clutch of kleptocrats continue to defraud citizens (as in Equatorial Guinea and Zimbabwe), upstart soldiers oust elected placeholders (Burkina Faso, Guinea, Mali), and here and there democratic stalwarts (Botswana, Ghana, Malawi, Senegal, South Africa, Zambia) are delivering authentic, uplifting, leadership to their followers.